Use of Educational Films in Environmental Education as a Digital Learning Object - Merve Topal; Ezgi Guven-Yildirim; Ayse Nesibe Onder (Journal of Education in Science, Environment and Health)
The purpose of this study is to investigate the effects of educational movies that are used in teaching the chapter of Mystery of Earth Crust / Earth and Universe on the environment-related knowledge levels and attitudes of students. Another purpose of the study is to find out about the views of students in the experiment. As a result of the study, the knowledge test mean scores of the students after the implementation significantly differed between the groups in favor of the experiment group. Another finding in this study, no significant difference was found between the groups in terms of their mean post-test attitude scores before the implementation. For the first question, the students stated that the Mystery of Earth Crust / Earth and Universe chapter was distinct from other chapters because of some differences. For the second question, the students stated that they learned the definition, reasons, effects and types of environmental pollution, gained awareness and responsibility about the environment, learned about behaviors towards preventing environmental pollution and developed an attitude towards environmental pollution. Additionally, with the third question the students’ emphasized educational movies had significant benefits for both individual outcomes and the instruction process